Analysis of The Injection Pressure Effect on Single Cylinder Diesel Engine Power with Diesel Fuel-Methanol Blend - Aguk Zuhdi Muhammad Fathallah; Adhi Iswantoro; Semin Semin; Beny Cahyono; I Made Ariana; Ananda Rizky Budi Pratama (International Journal of Marine Engineering Innovation and Research, 2022)
The use of fossil diesel fuels still produces carbon dioxide emissions (CO2), sulphur dioxide (SO2), hydrocarbon emissions (HC), nitrogen oxide (NOx), and high total particles and carbon monoxide (CO). Moreover, the need for transportation of motor vehicles will always increase every year. The emission of exhaust gases resulting from the combustion process can essentially be reduced by improving fuel quality, the homogeneity of the fuel mixture, and regulating proper combustion. There are several ways to reduce exhaust emissions from diesel engines by providing precise injection pressures. This is done to get the perfect combustion. In addition, improving fuel quality is a way to reduce emissions of exhaust gases. Another one is by adding methanol to the diesel. The addition of methanol can reduce the emission of exhaust gas produced. The process of mixing the solar and methanol takes the addition of surfactants to obtain good homogeneity. Testing was conducted using simulation software with engine modeling. The result can be seen in the reduction and the addition of standard pressure 200 bar, that the emulsion fuel in SFOC (specific fuel oil consumption) suffered a decrease and increased by 0.2% and 0.3% at pressure 160 bar and pressure 240 bar. The fuel solution on SFOC suffered a decrease and an increase of 0.3% and 0.25% was produced by pressure 160 bar and pressure 240 bar. The highest NOx is produced by 240 bar injection pressures with Dexlite fuel while the lowest NOx is produced by 160 bar injection pressure with emulsion fuel.